2016
DOI: 10.2527/jas.2016-0507
|View full text |Cite
|
Sign up to set email alerts
|

Deduction of a calcium ion circuit affecting rooster sperm in vitro1

Abstract: Four premises for rooster sperm preservation were outlined previously. Understanding mitochondrial Ca cycling in terms of whole-cell Ca flux was one premise. The present work tested the hypothesis that sperm mitochondria can be damaged by intracellular as well as extracellular Ca. Sperm were washed by centrifugation through 12% (wt/vol) Sperm were washed by centrifugation through 12%(at/vol) Accudenz to procure sperm at a physiological concentration within a chemically-defined suspension. Five solutions were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Previous studies have suggested that increased Ca 2+ permeability during cooling storage could have deleterious effects on sperm motility and fertilization potential in poultry 21 , 25 , 44 . Our results support this notion, demonstrating that an increase in [Ca 2+ ]i negatively regulates IPVL penetrability in a storage period–dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that increased Ca 2+ permeability during cooling storage could have deleterious effects on sperm motility and fertilization potential in poultry 21 , 25 , 44 . Our results support this notion, demonstrating that an increase in [Ca 2+ ]i negatively regulates IPVL penetrability in a storage period–dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm mitochondria play a vital role in coordinating ATP production, redox equilibrium, and calcium homeostasis, all of which can contribute to the regulation of sperm fertilization potential. Indicating a cross-genera conserved relevance, events that may be connected to mitochondrial impairments such as increased [Ca 2+ ] i levels, accumulation of reactive oxygen species (ROS), and decrease in mitochondrial membrane potential (ΔΨ M ) have been demonstrated to occur in the early stages of both liquid storage in chicken 20 , 21 and boar 22 , 23 semen. Nevertheless, specific mechanistic associations between increased [Ca 2+ ] i levels and reduced semen quality during storage or impact on mitochondrial function remain unknown.…”
Section: Introductionmentioning
confidence: 99%